SCHOOL SOCIAL ENVIRONMENT FACTORS AND ACADEMIC WELLBEING OF JUNIOR SECONDARY SCHOOL STUDENTS IN IBADAN RURAL COMMUNITIES - RAJI, Ismail Adesina; OWODUNNI, Abdulfatai Adekunle (Ilorin Journal of Education, 2023)
This study investigated the influence of school social environment factors on academic wellbeing (school value, school burnout, schoolwork engagement, satisfaction with educational choice) of JSS in Ibadan rural communities. The descriptive survey design was adopted. Multi-stage sampling frame was adopted. Four Local Government Areas (LGAs) were randomly selected. Twenty schools (four per LGA) were selected randomly, while 350 JSS3 students were selected using proportionate technique. The academic wellbeing (r = 0.88), supportive teacher relationship (r = 0.81), supportive students’ relationship (r = 0.74), supportive peer relationship (r = 0.71), disciplined learning environment (r = 0.83) and empathy (r = 0.76) rating scales were used to collect data. Descriptive statistics (mean and standard deviation), Pearson product moment coefficient and multiple regression were used to analysis data at 0.05 level of significance. School social environment (3.13 ± 1.37) of junior secondary school students in Ibadan rural communities was good with rooms for improvement, while academic well-being (1.84 ± 1.00) was low. The school social environment made significant contribution (68.7%) to the variations in the academic wellbeing of JSS3 students in Ibadan rural communities (Adjusted R2 = 0.687, F(5, 312) = 843.23). School principals in rural communities should create conducive school environment where social security is guaranteed for students, through good rapport with staff and sufficient attention to the feelings and academic needs of students.